Teologi Mesianik Perspektif Kristen dan Islam - Muhtar, Mohamad Khusnial (Al Hikmah, 2024)
In the messianic theology of Abrahamic religions such as Christianity and Islam, there is a view that in the end times, there will be a battle between good and evil, each represented by certain eschatological figures. This paper discusses the Messiah, the eschatological figure representing good, and the false messiah, representing evil, from the perspectives of Christianity and Islam. It attempts to compare and analyze in depth the concepts of the Messiah and the false messiah from Christian and Islamic perspectives in terms of their sources and historicity. Explicitly, this paper explains who and what the characteristics of the Messiah and the false messiah are that will appear towards the end of times from Christian and Islamic viewpoints. The method used in this paper is library research with a descriptive-qualitative approach. The results of this paper include that both Christianity and Islam recognize Jesus Christ or Isa Al-Masih as the messianic figure who will come towards the end of times. However, in the Islamic perspective, there is another figure associated as the messiah, namely Imam Mahdi. As for the false messiah, there are differences where Christianity associates it with the Antichrist and Islam with Dajjal, each having different characteristics and features. Regarding the discourse on the false messiah in both Christianity and Islam, it is highly interpretative. However, one thing is certain, he is recognized as a great deceiver.